Cognitive And Neurophysiological Correlates of English Language Learning: A Multidisciplinary Investigation - Parween, Shagufta; Jameer MD, Roshan; Yarlagadda, Saloman Raju; Emimal, M. Samadhanam; Kumuja, V Temuzion (Journal of Neonatal Surgery, 2025)
The acquisition of English as a second language (ESL) is a complex process influenced by cognitive and neurophysiological factors. This paper explores the cognitive mechanisms underpinning language learning, including working memory, executive functions, and attention, alongside the neurophysiological processes associated with neural plasticity, brain lateralization, and electrophysiological responses. The study integrates findings from cognitive psychology, neurolinguistics, and educational neuroscience to understand how the brain adapts to second language acquisition. It highlights the role of neuroimaging techniques such as functional magnetic resonance imaging (fMRI) and electroencephalography (EEG) in revealing brain activity patterns associated with English language learning. Furthermore, the impact of age, proficiency levels, and immersive learning environments on language processing is discussed. This multidisciplinary investigation offers insights into optimizing pedagogical strategies for ESL learners, emphasizing the importance of cognitive training and neurostimulation in enhancing language acquisition.